KESETARAAN PERAN SUAMI ISTRI DALAM ADAT PERKAWINAN SUKU BADUY DI DESA KANEKES LEUWIDAMAR KABUPATEN LEBAK BANTEN - Leni Anggraeni (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
This paper is examines the househould life of the Baduy tribe in Kanekes village, Leuwidamar sub-district, Lebak district, Banten province. The marriage custom of the Baduy tribe are interesting and unique. Therefore, it is interesting to study from the pre-marital process to marriage. They view marriage ritual as an agenda of sacred value to the stage of marriage and trust to work together without choosing and shorting out which jobs are appropriate and suitable for men and women. The purpose of this study was to determine the assumptions and theological meanings of the Baduy people regarding the practice of marriage in the Sunda Wiwitan religious tradition. Data was collected through interview, survey and documentation techniques. The result and conclutions of this study are that in the life of the community the position of women and mas is balanced. Husband and wife halp and complement each other in the household. The form of implementation and reality in the life of the Baduy tribe, for example, the work that is generally done by Baduy men is also often taken over and carried out by Baduy women and this has been developing for along time.